INTEGRATED APPROACHES FOR MANAGEMENT OF PEST COMPLEX IN POINTED GOURD (TRICHOSANTHES DIOICA ROXB) - P. BARMA; M. R. KHAN; S. JHA (The Bioscan, 2013)
The experiment was done to evaluate the efficacy and economics of different combination of treatments at different dosage against major pests of pointed gourd. Results of three consecutive seasons showed that the treatments T2 (carbosulfan 25EC + neem granule + NSKE 5%) and T4 (carbofuran 3G + propergite 7.5%) contained consistently lowest level of fruit fly, leaf roller and epilachna infestation. While T6 (carbosulfan 25EC + vermicompost + Paecilomyces lilacinus (PL) + dicofol 18.5 EC followed by propergite 7.5%) and T7 (carbosulfan 25EC + PL + dicofol) took much better care for root knot nematodes and mites infestation in pointed gourd. Further yield component was highest in these treatments than T4 or T2, which was not at all potent enough to decimate yield alarmingly. Considering incremental cost benefit ratio (ICBR), adoption of carbosulfan 25EC + azadirachtin 1% (T1) was found to be the most economical (ICBR 6.67 in 2007-08, 8.23 in 2008-09 and 8.18 in 2009-10). However, T6 would be an option where nematode egg parasitic fungus, P. lilacinus in combination with dicofol and propergite restrict both root knot nematode and red spider mite population development on the long duration crop like pointed gourd.